If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 27y + -3 Reorder the terms: 6x = -3 + 27y Solving 6x = -3 + 27y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = -0.5 + 4.5y Simplifying x = -0.5 + 4.5y
| (6*6)*(4*4*4)= | | 5(X-13)-7(6-X)+29=50-3(8-X) | | a+(a-8)=44 | | %.317=164 | | x^2+6.91830971e-7x-4e-8=0 | | x^2-3x/7x | | p+(-4)=1 | | 1a(105/(35/7)) | | 8x+8=9x-7 | | 3x+2x-5=x+7 | | 1/4×16 | | x^2+x-0.058=0 | | 48/165 | | 1/3(9x-12)=1/4(16x-12) | | 2x-5=3x-16 | | X/22=15/33 | | x+(x+1)+(x+2)=(x+3)+100 | | x+(x+1)+(x+2)=100 | | x-4=-x+6 | | 12/x=3/10 | | 3(7+10)+4(7+20)+5(7)=185-3(7) | | 2/6=6/x | | 4x+9=-4x+17 | | 3(7+10)+4(7+20)+5(x)=185-3(7) | | x+(x+2)+(x+3)=100 | | x^2-3/7 | | 6/c | | 5x+6=-3x+22 | | 3x-8=-6x+19 | | 8x+3=-2x-7 | | 2(y/3-y/5)=3+y/10 | | 2x+1=-5x-13 |